The Teleological Significance of the Sociological Method in the Study of Law as a Social Phenomenon - Mitrović, Aleksandra Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The aim of this scientific paper is to highlight the role and importance of the sociological method in the study of the law as a specific social phenomenon with its essence and structure—which need to be perceived as one—seeing that the law has both value and normative and social dimension. This stems from the relationship between rights and society, regarding the role that law has in the society and vice versa. As the nature of the object defines the method used to implement the process of research, the law as normatively shaped social phenomenon requires the use of sociological methods to explain the causes of partial or full (non) realization of legal norms in society. The conclusion is that a complex, dynamic, and variable substance and content of the law cannot be studied without the use of sociological methods, which, in addition to numerous methods of studying law, manage to investigate systematically and empirically the functional laws of the legal system as a social phenomenon.